2021
DOI: 10.1093/bioinformatics/btab155
|View full text |Cite
|
Sign up to set email alerts
|

Super-delta2: an enhanced differential expression analysis procedure for multi-group comparisons of RNA-seq data

Abstract: Motivation We developed super-delta2, a differential gene expression analysis pipeline designed for multi-group comparisons for RNA-seq data. It includes a customized one-way ANOVA F-test and a post-hoc test for pairwise group comparisons; both are designed to work with a multivariate normalization procedure to reduce technical noise. It also includes a trimming procedure with bias-correction to obtain robust and approximately unbiased summary statistics used in these tests. We demonstrated t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…While raw RNA-seq reads are discrete, common pre-processing steps can make the RNA-seq data much more normal. Recent comparative studies (Cui et al, 2021;Law et al, 2014;Rapaport et al, 2013;Ritchie et al, 2015;Smyth et al, 2005) showed that DGEA designed for continuous data can achieve comparable, sometimes even slightly better, performance than those based on discrete models. We plan to extend FastMix based on generalized linear mixed-effects regression, so that it can integrate high-dimensional data that cannot be approximated by normal distributions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While raw RNA-seq reads are discrete, common pre-processing steps can make the RNA-seq data much more normal. Recent comparative studies (Cui et al, 2021;Law et al, 2014;Rapaport et al, 2013;Ritchie et al, 2015;Smyth et al, 2005) showed that DGEA designed for continuous data can achieve comparable, sometimes even slightly better, performance than those based on discrete models. We plan to extend FastMix based on generalized linear mixed-effects regression, so that it can integrate high-dimensional data that cannot be approximated by normal distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous work on gene expression normalization (Cui et al, 2021;Liu et al, 2017;Qiu et al, 2013Qiu et al, , 2014, we know that trimming can introduce noticeable bias in statistical inference. We derive the trimmed and bias-corrected covariance estimates for B as follows…”
Section: Re-estimation and Bias Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these multi-group comparisons, the Tukey’s style post-hoc pairwise test were utilized to analysis the high-throughput experiments and a false discovery rate ( FDR ) - adjusted P < 0.05 was set as the cut-off [18] , [21] . These high-throughput experiments included ChIP-seq data and differentially expressed analysis on mRNA microarray data of macrophage polarization (GSE46903).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq data of 560 samples were covered in the transcriptome profiles for BLCA BC in TCGA database (TCGA-BLCA), containing 496 tumor tissues from patients with BC and 64 normal tissues from healthy volunteers. Edger & Limma/Voom were used to analyze differentially expressed genes in TCGA transcriptome data [ 19 ], and the conditions for screening differentially expressed genes were as following: | log (FC) | >1 & FDR < 0.05 or adj. p value <0.05.…”
Section: Methodsmentioning
confidence: 99%